Insights into the farming-season carbon budget of coastal earthen aquaculture ponds in southeastern China - Kam Tang (Agriculture, Ecosystems and Environment, 2022)
Small-hold aquaculture ponds are widespread in China, but their carbon greenhouse gas emissions are poorly quantified. In this study, we used a carbon budget approach to assess the climate footprint of three earthen aquaculture ponds in southeastern China with the whiteleg shrimp (Litopenaeus vannamei) during the farming period. The main carbon inputs to the ponds were planktonic primary production (58.5–61.8%), followed by commercial feeds (31.9-35.3%), while the major carbon outputs occurred through planktonic respiration (44.0–53.6%) and sedimentation (18.0–21.7%). Water-to-air emissions of carbon greenhouse gases (CO2 and CH4) represented only a small fraction of the carbon flow (0.8–1.6%), with a combined CO2-equivalent emission of 528.4±193.3 mg CO2-eq m−2 h−1 based on GWP20. We also observed significant spatio-temporal variation in carbon greenhouse gases among the three ponds, which could be attributed to the variation in Chl-a and carbon substrate supply. Nevertheless, the magnitude of CH4 emission from these ponds was still higher than some other agro-ecosystems. Moreover, we found that only 21% of the excess organic carbon was converted to shrimp biomass, while another 20% ended up in the sediment. Our findings suggested that lowering the feed conversion ratio and removing the bottom sediments regularly could help improve production efficiency, reduce the excessive accumulation of carbon-rich detritus and minimize the climatic warming impacts of aquaculture production.